O ekscentrycznej tożsamości spadkobierców Rzymu, czyli o tym jak niewielu jest dziś Europejczyków - Mathiesen, Aleksandra (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2014)
Taking under consideration Remi Brague’s point of view in a discussion of the European identity, the author of the article searches for a new insightful consideration on the problem of ‘being European’. In the cultural perspective the individual sense of belonging, creating an identity, depends on both historical and conscientious mechanisms, thus on the changeable factors affecting the individualities entangled in a struggle for ‘being European’. Therefore Brague introduced, instead of a ‘stable idea of Europe’ which European-to-be can relates to, the cultural form of ‘Roman attitude’ which remains crucial for creating the ‘European identity’. Actually, to put it bluntly, becoming an ‘heir of Rome’ is indispensable to become ‘European’, to exercise ‘Roman attitude’.
On the eccentric identity of heirs of Rome or how few Europeans have left
Keywords: European identity; the idea of Europe; Remi Brague; Roman attitude; eccentric identity